Discovery of Potent Inhibitors of Cyclin‐Dependent Kinases 7 and 9: Design, Synthesis, Structure‐Activity Relationship Analysis and Biological Evaluation. (27th November 2022) - Chen, Renjie; Hassankhani, Ramin; Long, Yi; Basnet, Sunita K. C.; Teo, Theodosia; Yang, Yuchao; Mekonnen, Laychiluh; Yu, Mingfeng; Wang, Shudong
Abstract: Cyclin‐dependent kinases (CDKs) 7 and 9 are deregulated in various types of human cancer and are thus viewed as therapeutic targets. Accordingly, small‐molecule inhibitors of both CDKs are highly sought‐after. Capitalising on our previous discovery of CDKI‐73, a potent CDK9 inhibitor, medicinal chemistry optimisation was pursued. A number of N ‐pyridinylpyrimidin‐2‐amines were rationally designed, chemically synthesised and biologically assessed. Among them, N ‐(6‐(4‐cyclopentylpiperazin‐1‐yl)pyridin‐3‐yl)‐4‐(imidazo[1, 2‐ a ]pyrimidin‐3‐yl)pyrimidin‐2‐amine was found to be one of the most potent inhibitors of CDKs 7 and 9 as well as the most effective anti‐proliferative agent towards multiple human cancer cell lines. The cellular mode of action of this compound was investigated in MV4‐11 acute myeloid leukaemia cells, revealing that the compound dampened the kinase activity of cellular CDKs 7 and 9, arrested the cell cycle at sub‐G1 phase and induced apoptosis. Abstract : Two targets : 4‐(Imidazo[1, 2‐ a ]pyrimidin‐3‐yl)‐ N ‐pyridinylpyrimidin‐2‐amines were found to be not only potent inhibitors of cyclin‐dependent kinases (CDKs) 7 and 9 but also effective anti‐proliferative agents against a range of human cancer cell lines. The findings from cellular mechanistic studies support that the observed anti‐proliferative effect could originate from the inhibition of both CDKs.A previous version of this manuscript has been deposited on a preprint server (https://doi.org/10.2139/ssrn.4210989 ).